Gender Reform in Pesantren Leadership in Madura: From Patriarchal Domination to Matriarchy - Sutrisno, Andri; Encung, Encung (Proceedings of International Conference on Muslim Society and Thought, 2024)
Pesantren in Madura traditionally have a patriarchal leadership structure, where men, especially kiai, dominate leadership and decision-making positions. However, along with social change and increased awareness of gender equality, there has been a paradigm shift towards the inclusion and empowerment of women in pesantren leadership. This study aims to understand and analyze the stages of patriarchy to matriarchy change in Madurese boarding schools, to understand and analyze the paradigm shift in determining leaders in Madurese boarding schools, and to analyze the supporting and inhibiting factors in the practice of matriarchy in Madurese boarding schools. This research is a descriptive qualitative research with a case study research type. The data collection techniques used observation, interview and documentation techniques. While the data analysis uses data reduction, data presentation and conclusion drawing. The results of this study are that the stages of changing patriarchy to matriarchy in madura Islamic boarding schools go through the initiation stage, adaptation stage and implementation stage. As for the paradigm shift in determining leaders in Madurese boarding schools with increased access to education, gender awareness, the influence of globalization and socio-cultural dynamics. While the supporting factors in the practice of matriarchy are through massive education, an increase in women’s education, the dynamics of internal pesantren problems and inhibiting factors due to resistance from conservative groups, gender bias and gender stereotypes.